Development and feasibility testing of a digital discharge planning application for fall risk prevention - Mustikaningsih; Suroso, Jebul; -, Yektiningtyastuti; Purwito, Dedy (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Patient falls remain a major safety concern in hospital settings, particularly during care transitions and after discharge. Conventional discharge education is often unstructured, inconsistently delivered, and difficult for patients and families to revisit after leaving the hospital. In addition, the limited availability of integrated digital tools constrains effective patient education, documentation, and monitoring, highlighting the need for innovative discharge planning solutions. Objective: This study aimed to develop and evaluate the feasibility of a digital discharge planning application for fall risk prevention, with a focus on improving patient knowledge and nurse compliance. Methods: This development study employed a needs-based design approach to create a mobile application integrating fall risk assessment, structured discharge education, and nurse compliance monitoring within a unified digital system. Preliminary evaluation used a pre-experimental one-group pretest–posttest design involving 30 hospitalized patients at risk of falls and 30 nurses. Patient knowledge was assessed using a 10-item questionnaire, while nurse compliance was measured using a structured checklist. Data were analyzed using the Wilcoxon signed-rank test. Results: The developed application, named “Si-Patuh,” demonstrated good usability and practical applicability in clinical settings. Patient knowledge scores increased significantly from a median of 0 (range: 0–5) before intervention to 10 (range: 7–10) after intervention (Z = –4.837; p < 0.001; r = 0.88). Nurse compliance scores also improved significantly from a median of 5 (range: 0–10) to 10 (range: 9–10) (Z = –4.563; p < 0.001; r = 0.83). The application effectively integrated patient education and nurse adherence within a structured digital discharge planning framework. Conclusion: The application is a feasible, innovative solution for strengthening discharge planning by improving patient knowledge and nurse compliance with fall prevention. This integrated digital approach has the potential to enhance patient safety and continuity of care in hospital settings.